Pengaruh Tata Kelola, Komitmen Organisasi dan Reward terhadap Penerapan Anggaran Berbasis Kinerja pada Provinsi Sumatera Barat - Yunisa Gusria Annur; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to obtain empirical evidence and determine the effect of governance, organizational commitment and rewards on the implementation of performance-based budgeting. The population in this study was OPD in West Sumatra Province with 100 samples taken. The sampling technique used total sampling. The source of data in this study is primary data with data collection techniques using questionnaires. The data analysis method in this study uses multiple linear regression analysis with the application of performance-based budgeting as the dependent variable and governance, organizational commitment and reward as independent variables. The results of this study indicate that governance, organizational commitment and rewards have no effect on the implementation of performance-based budgeting.